2011
DOI: 10.1111/j.1440-1746.2011.06737.x
|View full text |Cite
|
Sign up to set email alerts
|

Additive improvement induced by bezafibrate in patients with primary biliary cirrhosis showing refractory response to ursodeoxycholic acid

Abstract: Higher ALP level at diagnosis is one of the predictors for UDCA failure. Combination treatment of bezafibrate in addition to UDCA may be an effective treatment for PBC patients refractory to UDCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…Although UDCA is currently the only drug approved for the treatment of PBC, bezafibrate has been widely used in Japanese patients with an inadequate response to UDCA treatment alone since the first report of a favorable effect with bezafibrate was observed in Japanese PBC patients . Bezafibrate is effective in approximately 80% of PBC patients in whom liver enzymes do not normalize on UDCA monotherapy within 6 months . However, the long‐term effects of bezafibrate are not yet clearly established, and criteria for interpreting the biochemical response to bezafibrate have not been defined to date.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although UDCA is currently the only drug approved for the treatment of PBC, bezafibrate has been widely used in Japanese patients with an inadequate response to UDCA treatment alone since the first report of a favorable effect with bezafibrate was observed in Japanese PBC patients . Bezafibrate is effective in approximately 80% of PBC patients in whom liver enzymes do not normalize on UDCA monotherapy within 6 months . However, the long‐term effects of bezafibrate are not yet clearly established, and criteria for interpreting the biochemical response to bezafibrate have not been defined to date.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Bezafibrate in combination with UDCA was recently found to be effective for normalizing serum levels of liver enzymes, especially ALP and IgM. [22][23][24][25] Although UDCA is currently the only drug approved for the treatment of PBC, bezafibrate has been widely used in Japanese patients with an inadequate response to UDCA treatment alone since the first report of a favorable effect with bezafibrate was observed in Japanese PBC patients. 22 Bezafibrate is effective in approximately 80% of PBC patients in whom liver enzymes do not normalize on UDCA monotherapy within 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1999, Iwasaki et al [9] firstly performed a pilot study with 11 precirrhotic patients with PBC and demonstrated the biochemical effectiveness of bezafibrate in PBC. Thereafter, a number of studies, most of which were performed in Japan, have demonstrated biochemical efficacy of bezafibrate in patients with suboptimal response to UDCA [10][11][12][13][14][15][16][17][18][19][20], including two randomized controlled prospective studies [21,22], and as a result, bezafibrate has been empirically recognized as a second-line therapy for PBC in Japan [3]. However, most of these clinical reports had substantial limitations which might impair supporting the role of bezafibrate as an alternative treatment in PBC.…”
Section: Introductionmentioning
confidence: 99%
“…Because our study was performed using several modalities to screen HCC and the screening interval is 6 to 12 months, we assessed the comparability of the ratio of types of modalities to screen HCC, the screening intervals and the ratio of combination of modalities, and the screening intervals between the patients who had developed HCC and those who had not developed HCC. On the other hand, ursodeoxycholic acid improves prognosis in view of liver biochemistry, histological progression, the development of portal hypertension and its complications [1418], and combination of ursodeoxycholic acid and bezafibrate [1921] or bezafibrate alone [21, 22] are effective for PBC. Moreover, several observational studies [18, 2327] have shown that the long-term outcome of PBC correlates with the biochemical response to ursodeoxycholic acid.…”
Section: Methodsmentioning
confidence: 99%